Inhibitory effect of anti-malarial agents on the expression of proinflammatory chemokines via Toll-like receptor 3 signaling in human glomerular endothelial cells. Issue 1 (1st January 2021) - Sato, Riko; Imaizumi, Tadaatsu; Aizawa, Tomomi; Watanabe, Shojiro; Tsugawa, Koji; Kawaguchi, Shogo; Seya, Kazuhiko; Matsumiya, Tomoh; Tanaka, Hiroshi
Abstract: Objective: Although anti-malarial agents, chloroquine (CQ) and hydroxychloroquine (HCQ) are currently used for the treatment of systemic lupus erythematosus, their efficacy for lupus nephritis (LN) remains unclear. Given that upregulation of glomerular Toll-like receptor 3 (TLR3) signaling plays a pivotal role in the pathogenesis of LN, we examined whether CQ and HCQ affect the expression of the TLR3 signaling-induced representative proinflammatory chemokines, monocyte chemoattractant protein-1 (MCP-1), and C–C motif chemokine ligand 5 (CCL5) in cultured human glomerular endothelial cells (GECs). Methods: We examined the effect of polyinosinic-polycytidylic acid (poly IC), an agonist of TLR3, on MCP-1, CCL5 and interferon (IFN)-β expression in GECs. We then analyzed whether pretreatment with CQ, HCQ, or dexamethasone (DEX) inhibits poly IC-induced expression of these chemokines using real-time quantitative reverse transcriptase PCR and ELISA. Phosphorylation of signal transducers and activator of transcription protein 1 (STAT1) was examined using western blotting. Results: Poly IC increased MCP-1 and CCL5 expression in a time- and concentration-dependent manner in GECs. Pretreating cells with CQ, but not DEX, attenuated poly IC-induced MCP-1 and CCL5 expression; however, HCQ pretreatment attenuated poly IC-induced CCL5, but not MCP-1. HCQ did not affect the expression of IFN-β and phosphorylation of STAT-1. Conclusion: Considering that TLR3 signaling is implicated, at least in part, in LN pathogenesis, our results suggest that anti-malarial agents exert a protective effect against the development of inflammation in GECs, as postulated in LN. Interestingly, CQ is a rather powerful inhibitor compared with HCQ on TLR3 signaling-induced chemokine expression in GECs. In turn, these findings may further support the theory that the use of HCQ is safer than CQ in a clinical setting. However, further detailed studies are needed to confirm our preliminary findings.